Hadith #2174 - Sunan Abi Dawud - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ammar bin Razayq عمار بن رزيق; Ikrama عكرمة; Yahya bin Y'amar يحيى بن يعمر; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
AbuNadrah reported: An old man of Tufawah said to me: I was a guest of AbuHurayrah at Medina. I did not find any one of the companions of the Prophet (ﷺ) more devoted to worship and more hospitable than AbuHurayrah. One day I was with him when he was sitting on his bed. He had a purse which contained pebbles or kernels. A black slave-girl of his was sitting below. Counting them he was glorifying Allah. When the pebbles or the kernels in the purse were finished, she gathered them and put them a
Grade: Da'if

Hadith #2182 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Ma'mar bin Rashid معمر بن راشد; Yonus bin Jubayr al-Bahli, Abu Ghalab يونس بن جبير الباهلي أبو غلاب (Sunan Abi Dawud)
‘Abd Allah (bin Umar) said that he divorced his wife while she was menstruating. ‘Umar mentioned the matter to the Messenger of Allah(ﷺ). The Messenger of Allah(ﷺ) became angry and said “Command him, he must take her back and keep her back till she is purified, then has another menstrual period and is purified. Then if he desires he may divorce her during the period of purity before he has intercourse with her. This is the divorce for waiting period as commanded by Allaah, the Exalted.
Grade: Sahih

Hadith #2203 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A’ishah said The Apostle of Allaah(ﷺ) gave us our choice and we chose him so that was not reckoned anything (i.e., divorce)
Grade: Sahih

Hadith #2213 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Ishaq محمد بن إسحاق بن يسار‎; Ma'mr bin 'Abdullah معمر بن عبد الله بن حنظلة; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yusuf bin 'Abdullah bin Salam (Sunan Abi Dawud)
I was a man who was more given than others to sexual intercourse with women. When the month of Ramadan came, I feared lest I should have intercourse with my wife, and this evil should remain with me till the morning. So I made my wife like my mother’s back to me till the end of Ramadan. But one night when she was waiting upon me, something of her was revealed. Suddenly I jumped upon her. When the morning came I went to my people and informed them about this matter. I said: Go along with me to
Grade: Hasan

Hadith #2214 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Abi Dawud)
My husband, Aws ibn as-Samit, pronounced the words: You are like my mother. So I came to the Messenger of Allah (ﷺ), complaining to him about my husband. The Messenger of Allah (ﷺ) disputed with me and said: Remain dutiful to Allah; he is your cousin. I continued (complaining) until the Qur’anic verse came down: “Certainly has Allah heard the speech of the one who argues with you, till the prescription of expiation. He then said: He should set free a slave. She said: He cannot afford it.
Grade: Hasan

Hadith #2255 - Sunan Abi Dawud - Aabad bin Mnswr عباد بن منصور; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; ibn Abbas; Ikrama عكرمة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
When the Prophet (ﷺ) ordered a man and his wife to invoke curses on each other, he ordered a man to put his hand on his mouth when he came to the fifth utterance, saying that it would be the deciding one.
Grade: Sahih

Hadith #2260 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
Abu Hurairah said A man from Banu Fazarah came to the Prophet (ﷺ) and said “My wife has given birth to a black son”. He said “Have you any camels?” He said “They are red”. He asked “Is there a dusky one among them?” He replied “Some of them are dusky”. He asked “How do you think they have come about?” He replied “This may be a strain to which they reverted”. He said “And this is perhaps a strain to which the child has reverted.”
Grade: Sahih

Hadith #2276 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hilal bin Abi Maymuna هلال بن علي بن أسامة; Ibn Jurayj ابن جريج; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
A woman said: Messenger of Allah, my womb is a vessel to this son of mine, my breasts, a water-skin for him, and my lap a guard for him, yet his father has divorced me, and wants to take him away from me. The Messenger of Allah (ﷺ) said: You have more right to him as long as you do not marry.
Grade: Hasan

Hadith #2326 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; ibn Abbas; Ikrama عكرمة; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not fast (for Ramadan) before the coming of the month until you sight the moon or complete the number (of thirty days); then fast until you sight the moon or complete the number (of thirty days).
Grade: Sahih

Hadith #2390 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Da'ud أبو داود السجستاني الأزدي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and said: I am undone. He asked him: What has happened to you ? He said: I had intercourse with my wife in Ramadan (while I was fasting). He asked: Can you set a slave free ? He said: No. He again asked: Can you fast for two consecutive months ? He said: No. He asked: Can you provide food for sixty poor people ? He said: No. He said: Sit down. Then a huge basket containing dates (‘araq) was brought to the Prophet (ﷺ). He then said to him: Give it as sadaqah (i
Grade: Sahih

Hadith #2418 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Jarrah bin Malih bin 'Ady الجراح بن مليح بن عدي; Uqba bin 'Amir al-Juhayni; Uthman bin Muhammad; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Eat. He said: I am fasting. ‘Amr said: Eat, these are the days on which the Messenger of Allah (ﷺ) used to command us to break fast, and forbid us to keep fast. The narrator Malik said: These are the day of al-tashriq (i.e. 11th, 12th, and 13th of Dhu al-Hijjah).
Grade: Sahih

Hadith #2426 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
He said: Messenger of Allah, tell me about keeping fast on Monday and Thursday. He said: On it I was born, and on it the Qur’an was first revealed to me.
Grade: Sahih

Hadith #2457 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
Some food was presented to me and Hafsah. We were fasting, but broke our fast. Then the Messenger of Allah (ﷺ) entered upon us. We said to him: A gift was presented to us; we coveted it and we broke our fast. The Messenger of Allah (ﷺ) said: There is no harm to you; keep a fast another day in lieu of it.
Grade: Da'if

Hadith #2539 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Musa bin Y'aqub bin 'Abdullah bin Wahb موسى بن يعقوب بن عبد الله بن وهب; Sa'id bin Abi Maryam سعيد بن أبي مريم; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
AbuSalam reported on the authority of a man from the companion of the Prophet (ﷺ). He said: We attacked a tribe of Juhaynah. A man from the Muslims pursued a man of them, and struck him but missed him. He struck himself with the sword. The Messenger of Allah (ﷺ) said: Your brother, O group of Muslims. The people hastened towards him, but found him dead. The Messenger of Allah (ﷺ) wrapped him with his clothes and his blood, and offered (funeral) prayer for him and buried him. They said: Mes
Grade: Da'if

Hadith #2598 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) proceeded on journey, he would say: O Allah, Thou art the Companion in the journey, and the One Who looks after the family; O Allah, I seek refuge in Thee from the difficulty of travelling, finding harm when I return, and unhappiness in what I see coming to my family and property. O Allah, make the length of his journey short for us, and the journey easy for us.
Grade: Sahih

Hadith #2600 - Sunan Abi Dawud - Abu Ja'far al-Khutami, 'Umayr bin Yazid عمير بن يزيد أبو جعفر الخطمي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Salama حماد بن سلمة; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yahya bin Ishaq يحيى بن إسحاق (Sunan Abi Dawud)
Qaza’ah said Ibn ‘Umar told me “Come, I see off you as the Apostle of Allaah(ﷺ) saw me off. I entrust to Allaah your religion what you are responsible for and your final deeds.”
Grade: Sahih

Hadith #2637 - Sunan Abi Dawud - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي (Sunan Abi Dawud)
When the Prophet (ﷺ) intended to go on an expedition, he always pretended to be going somewhere else, and he would say: War is deception. Abu Dawud said: Only Ma’mar has transmitted this tradition. By this he refers to his statement “War is deception” through this chain of narrators. He narrated it from the tradition of ‘Amr b. Dinar from Jabir, and from the tradition of Ma’mar from Hammam b. Munabbih on the authority of Abu Hurairah.
Grade: Sahih

Hadith #2652 - Sunan Abi Dawud - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) commanded to kill him: he was a spy of AbuSufyan and an ally of a man of the Ansar. He passed a circle of the Ansar and said: I am a Muslim. A man from the Ansar said, Messenger of Allah, he is saying that he is a Muslim. The Messenger of Allah (ﷺ) said: There are people among you in whose faith we trust. Furat ibn Hayyan is one of them.
Grade: Sahih

Hadith #2798 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) distributed sacrificial animals among his Companions. He gave me a kid (of less than a year). I took it to him and said: This is a kid. He said: Sacrifice it. so I sacrificed it.
Grade: Hasan Sahih

Hadith #2831 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Prophet (ﷺ) sa saying: There is no fara’ and ‘atirah.
Grade: Sahih

Hadith #2838 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hafsa bint Sirin حفصة بنت سيرين; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي (Sunan Abi Dawud)
The Prophet (ﷺ) said: A boy is in pledge for his Aqiqah, Sacrifice is made for him on the seventh day, his head is shaved and he is given name. Abu Dawud said: The word wa yusamma is sounder as narrated by Salam b. Abi Muti’ from Qatadah, and narrated by Iyas b. Daghfal and Ash’ath from al-Hassan who narrated wa yusamma (and he is given a name).
Grade: Sahih

Hadith #2843 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
When a boy was born to one of us in the pre-Islamic period, we sacrificed a sheep and smeared his head with its blood; but when Allah brought Islam, we sacrificed a sheep, shaved his head and smeared his head with saffron.
Grade: Hasan Sahih

Hadith #2867 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Salm bin Abi Salm سالم بن أبي سالم; Ubaidullah bin Abi Ja'far عبيد الله بن أبي جعفر المصري (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man or a woman acts in obedience to Allah for sixty years, then when they are about to die they cause injury by their will, so they must go to Hell. Then AbuHurayrah recited: “After a legacy which you bequeath or a debt, causing no injury…that will be the mighty success. Abu Dawud said: Al-Ash’ath b. Jabir is the grandfather of Nasr b. ‘Ali.
Grade: Hasan

Hadith #3029 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Umar ibn al-Khattab (Sunan Abi Dawud)
Ibn ‘Abbas said that the Prophet (ﷺ) gave three instructions saying “Expel the polytheists from Arabia, reward deputations as I did”. Ibn ‘Abbas said “He either did not mention the third or I have been caused to forget it. Al Humaidi said on the authority of Sufyan that Sulaiman said “I do not know whether Sa’id mentioned the third and I forgot or he himself did not mention it.”
Grade: Sahih

Hadith #3113 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say three days before his death: No one of you dies but he had good faith in Allah.
Grade: Sahih

Hadith #3223 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
One day the Messenger of Allah (ﷺ) went out and prayed over the martyrs of Uhud like his prayer over the dead, and then returned.
Grade: Sahih

Hadith #3246 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) said: One should not take a false oath at this pulpit of mine even on a green tooth-stick; otherwise he will make his abode in Hell, or Hell will be certain for him.
Grade: Sahih

Hadith #3265 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Asim bin Lqyt bin 'Amir عاصم بن لقيط بن عامر بن المنتفق; Ibrahim bin Hamza bin Muhammad إبراهيم بن حمزة بن محمد (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) swore an oath, it was: No, and I beg forgiveness of Allah.
Grade: Da'if

Hadith #3313 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Maymuna bin Kardam; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
In the time of the Prophet (ﷺ) a man took a vow to slaughter a camel at Buwanah. So he came to the Prophet (ﷺ) and said: I have taken a vow to sacrifice a camel at Buwanah. The Prophet (ﷺ) asked: Did the place contain any idol worshipped in pre-Islamic times? They (the people) said: No. He asked: Was any pre-Islamic festival observed there? They replied: No. The Prophet (ﷺ) said: Fulfil your vow, for a vow to do an act of disobedience to Allah must not be fulfilled, neither must one do s
Grade: Sahih

Hadith #3348 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Gold for gold is interest unless both hand over on the spot ; wheat for wheat is interest unless both hand over on the spot ; dates for dates is interest unless both hand over on the spot ; barley for barley is interest unless both hand over on the spot.
Grade: Sahih

Hadith #3370 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade the sale of fruits until they are ripened (tushqihah). He was asked: What do you mean by their ripening (ishqah)? He replied: They become red or yellow, and they are eaten.
Grade: Sahih

Hadith #3377 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Sa'id al-Khudri; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) forbade two types of business transactions and two ways of dressing. The two types of business transactions are mulamasah and munabadhah. As regards the two ways of dressing, they are the wrapping of the samma’, and that when a man wraps himself up in a single garment while sitting in such a way that he does not cover his private parts or there is no garment on his private parts.
Grade: Sahih

Hadith #3418 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Ibn Sirin محمد بن سيرين الأنصاري; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
Some of the Companions of Prophet (ﷺ) went on a journey. They encamped with a clan of the Arabs and sought hospitality from them, but they refused to provide them with any hospitality. The chief of the clan was stung by a scorpion or bitten by a snake. They gave him all sorts of treatment, but nothing gave him relied. One of them said: Would that you had gone to those people who encamped with you ; some of them might have something which could give you relief to your companion. (So they went a
Grade: Sahih

Hadith #3497 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone buys a grain, he should not sell it until he takes possession of it. Sulaiman b. Harb said: Until he receives it in full. Musaddad added: Ibn ‘Abbas said: And I think that everything is like grain.
Grade: Sahih

Hadith #3605 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; ibn Abbas; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan Abi Dawud)
A Muslim was about to die at Daquqa’, but he did not find any Muslim to call him for witness to his will. So he called two men of the people of the Book for witness. Then they came to Kufah, and approaching AbuMusa al-Ash’ari they informed him (about his) will. They brought his inheritance and will. Al-Ash’ari said: This is an incident (like) which happened in the time of the Messenger of Allah (ﷺ) and never occurred after him. So he made them to swear by Allah after the afternoon prayer
Grade: Da'if

Hadith #3613 - Sunan Abi Dawud - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Two men claimed a camel or an animal and brought the case to the Holy Prophet (ﷺ). But as neither of them produced any proof, the Holy Prophet (ﷺ) declared that they should share it equally.
Grade: Hasan

Hadith #3656 - Sunan Abi Dawud - Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Bakr bin 'Amr al-Ma'fari بكر بن عمرو المعافري; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي (Sunan Abi Dawud)
The Holy Prophet (ﷺ) forbade the discussion of thorny questions.
Grade: Da'if

Hadith #3675 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Nu'man bin Bashir ibn Sa'd; Amir al-Sha'bi عامر الشعبي; Ibrahim bin Mhajr bin Jabir إبراهيم بن مهاجر بن جابر; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Abu Talhah asked the prophet (ﷺ) about the orphans who had inherited wine. He replied: Pour it out. He asked: May I not make vinegar of it ? He replied : No.
Grade: Sahih

Hadith #3700 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
The Prophet(ﷺ) mentioned the vessels: pumpkins, green jarrs, vessels smeared with pitch and hollow stumps. A desert Arab said: We have no vessels(except these). He said: Drink(from them) what is lawful.
Grade: Sahih

Hadith #3714 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
I find the smell of gum (maghafir) from you. He then entered upon one of them; she said that to him. Thereupon he said : No, I drank honey at (the house of) Zainab daughter of jahsh, and I will not do it again. Then the following verse came down :’’O Prophet !why holdest thou to be forbidden that which Allah has made lawful to thee ? ‘’Thou seekest. . . If you two turn in repentance to Allah ‘’ refers to Hafsah and A’ishah , and the verse: ‘’When the Prophet disclosed a matter
Grade: Sahih

Hadith #3737 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
If he is not fasting, he should eat, and if he is fasting, he should leave it.
Grade: Sahih

Hadith #3945 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan Abi Dawud)
The tradition mentioned above has also been narrated by Ibn ‘Umar through a different chain of transmitters to the same effect as mentioned by Malik. In this version there is no mention of the words “otherwise he will be emancipated to the extent of the first man’s share.” His version ends “and the slave be thus emancipated,” to the same effect as he (Malik) mentioned.
Grade: Sahih

Hadith #4076 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Ja'far bin 'Amr bin Hryth جعفر بن عمرو بن حريث; Msawr al-Wraq al-Kwfy al-Sha'r مساور الوراق الكوفي الشاعر (Sunan Abi Dawud)
The Prophet (ﷺ) entered Mecca in the year of the Conquest while he had a black turben over him.
Grade: Sahih

Hadith #4159 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade combing the hair except every second day.
Grade: Sahih

Hadith #4196 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
I had a hanging lock of hair. My mother said to me: I shall not cut it, for the Messenger of Allah (ﷺ) used to stretch it our and hold it.
Grade: Da'if

Hadith #4204 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abdur-Razzaq عبد الرزاق بن همام; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Abu Dharr al-Ghaffari; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ma'mar bin Rashid معمر بن راشد; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan Abi Dawud)
Abu Quhafah was brought on the day of the conquest of Mecca with head and beard while like hyssop. The Messenger of Allah (ﷺ) said: Change this something, but avoid black.
Grade: Sahih

Hadith #4232 - Sunan Abi Dawud - Abu al-Ashhab al-Atardi جعفر بن حيان أبو الأشهب العطاردي; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
AbdurRahman ibn Tarafah said that his grandfather Arfajah ibn As’ad who had his nose cut off at the battle of al-Kilab got a silver nose, but it developed a stench, so the Prophet (ﷺ) ordered him to get a gold nose.
Grade: Hasan

Hadith #4353 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Bryd bin 'Abdullah بريد بن عبد الله بن أبي; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) Said: The blood of a Muslim man who testifies that there is no god but Allah and that Muhammad is Allah’s Apostle should not lawfully be shed except only for one of three reasons: a man who committed fornication after marriage, in which case he should be stoned; one who goes forth to fight with Allah and His Apostle, in which case he should be killed or crucified or exiled from the land; or one who commits murder for which he is killed.
Grade: Sahih

Hadith #4426 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Ma’iz ibn Malik came to the Prophet (ﷺ) and admitted fornication twice. But he drove him away. He then came and admitted fornication twice. But he drove him away. He then came and admitted fornication twice. He (the Prophet) said: You have testified to yourself four times. Take him away and stone him to death.
Grade: Sahih

Hadith #4427 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) said to Ma’iz ibn Malik: Perhaps you kissed, or squeezed, or looked. He said: No. He then said: Did you have intercourse with her? He said: Yes. On the (reply) he (the Prophet) gave order that he should be stoned to death. The narrator did not mention “on the authority of Ibn ‘Abbas”. This is Wahb’s version.
Grade: Sahih

Hadith #4487 - Sunan Abi Dawud - Abdur Rahman bin Azhar bin 'Abd 'Awf; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Usamah ibn Zayd; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس (Sunan Abi Dawud)
I can still picture myself looking at the Messenger of Allah (ﷺ) who was among the camps of the Companions seeking the camp of Khalid ibn al-Walid, when a man who had drunk wine was brought before him. He asked the people: Beat him. Some struck him with sandals, some with sticks and some with fresh branches of the palm-tree (mitakhah). Ibn Wahb said: This (mitakhah) means green palm fronds. Then the apostle of Allah (ﷺ) took some dust from the ground and threw it on his face.
Grade: Hasan Sahih

Hadith #4515 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Sa'id bin 'Amir al-Dab'ai سعيد بن عامر الضبعي; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
The Prophet (ﷺ) Said: If anyone kills his slave, we shall kill him, and if anyone cuts off the nose of his slave, we shall cut off his nose.
Grade: Da'if

Hadith #4522 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Rafi' bin Khadij bin Rafi'; Ubaya bin Rafa' bin Rafi' عباية بن رفاعة بن رافع; Yahya bin Sa'id bin Hiyan يحيى بن سعيد بن حيان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) killed a man of Banu Nadr ibn Malik at Harrah ar-Righa’ at the bank of Layyat al-Bahrah. The transmitter Mahmud (ibn Khalid) also mentioned the words along with the words “at Bahrah” “the slayer and the slain were from among them”. Mahmud alone transmitted in this tradition the words “at the bank of Layyah”.
Grade: Da'if

Hadith #4524 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan Abi Dawud)
A man of the Ansar was killed at Khaybar and his relatives went to the Prophet (ﷺ) and mentioned that to him. He asked: Have you two witnesses who can testify to the murderer of your friend? They replied: Messenger of Allah! there was not a single Muslim present, but only Jews who sometimes have the audacity to do even greater crimes than this. He said: Then choose fifty of them and demand that they take an oath; but they refused and the Prophet (ﷺ) paid the blood-wit himself.
Grade: Sahih

Hadith #4661 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
When the Prophet (May peace be upon him) heard ‘Umar’s voice, Ibn Zam’ah said: The Prophet (May peace be upon him) came out until he took out his head of his apartment. He then said : No, no, no; the son of Abu Quhafah should lead the people in prayer. He said it angrily.
Grade: Sahih

Hadith #4714 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hajjaj bin al-Minhal حجاج بن المنهال; Hammad bin Salama حماد بن سلمة (Sunan Abi Dawud)
Every child is born on Islam, but his parents make him a Jew and a Christian, just as a beast is born whole. Do you find some among them (born) maimed? The people asked : Messenger of Allah! What do you think about the one who died while he was young? He replied : Allah knows best what he was going to do.
Grade: Sahih

Hadith #4764 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Anas ibn Malik; Ma'mar bin Rashid معمر بن راشد; Qatada قتادة (Sunan Abi Dawud)
‘Ali sent some gold-mixed dust to the prophet (May peace be upon him). He divided it among the four : al-Aqra b. Habis al-Hanzall and then al-Mujashi, uyainah b. Badr al-fazari, zaid al-khail al-Ta’l, next to one of Banu nabhan, and ‘Alqamah b. ‘Ulathat al-Amiri (in general), next to one of Banu kulaib. The Quraish and the ansar became angry and said : He is giving to the chiefs of the people of Najd and leaving us. He said : I am giving them for reconciliation of their hearts. Then a ma
Grade: Sahih

Hadith #4766 - Sunan Abi Dawud - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Zayd bin Wahb al-Jhny زيد بن وهب الجهني (Sunan Abi Dawud)
Tasmid means uprooting the hair.
Grade: Sahih

Hadith #4921 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Anas ibn Malik; Ma'mar bin Rashid معمر بن راشد; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I did not hear the Messenger of Allah (ﷺ) making a concession for anything people say falsely except in three matters. The Messenger of Allah (ﷺ) would say: I do not count as a liar a man who puts things right between people, saying a word by which he intends only putting things right, and a man who says something in war, and a man who says something to his wife, or a wife who says something to her husband.
Grade: Sahih

Hadith #5026 - Sunan Abi Dawud - Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Sa'id bin Abi Sa'id; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
When one of you yawns, he should hold his hand over his mouth, for the devil enters.
Grade: Sahih

Hadith #5168 - Sunan Abi Dawud - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ammar bin Razayq عمار بن رزيق; Ikrama عكرمة; Yahya bin Y'amar يحيى بن يعمر; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
I came to Ibn ‘Umar when he set his slave free. He took a stick or something else from the earth and said; for me there is no reward even equivalent to this. I heard the Messenger of Allah (May peace be upon him) say: If anyone slaps or beats his slave the atonement due from him is to set him free.
Grade: Sahih

Hadith #5208 - Sunan Abi Dawud - Abdul Malik bin Ibrahim al-Jaddi عبد الملك بن إبراهيم الجدي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ali ibn Abi Talib; Sa'id bin Khalid al-Khza'y سعيد بن خالد الخزاعي المدني; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you comes to an assembly, he should give a salutation and if he feels inclined to get up, he should give a salutation, for the former is not more of a duty than the latter.
Grade: Hasan Sahih